2022
DOI: 10.1002/jpen.2351
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional outcomes of patients with pediatric and congenital heart disease requiring ventricular assist devices

Abstract: Background Ventricular assist devices (VADs) support children with heart failure. The objective is to report on the nutrition outcomes of children requiring VAD. Methods This was a retrospective study performed in a tertiary care center. All patients undergoing VAD placement from 2010 to 2018 were included. Exclusion criteria were VAD placement in outside hospitals, missing baseline anthropometrics, and death in the first 15 days post‐VAD. Clinical, demographic, and nutrition data were collected from baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…This is similar to reports from previous studies that reported the incidence of malnutrition in pre‐Fontan patients as 19% by WAZ 8 and 9%–18% by WAZ/HAZ 2 . This is much higher than the prevalence reported for hospitalized children in the United States based on administrative data but similar to what has been reported in children with heart failure listed for transplant and in those requiring a ventricular assist device 9,10 . Unlike the heart failure population, moderate‐severe malnutrition persisted in this Fontan population over time, with an average of 1 in 10 patients still meeting the criteria for malnutrition at 10‐years post‐Fontan surgery 10 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is similar to reports from previous studies that reported the incidence of malnutrition in pre‐Fontan patients as 19% by WAZ 8 and 9%–18% by WAZ/HAZ 2 . This is much higher than the prevalence reported for hospitalized children in the United States based on administrative data but similar to what has been reported in children with heart failure listed for transplant and in those requiring a ventricular assist device 9,10 . Unlike the heart failure population, moderate‐severe malnutrition persisted in this Fontan population over time, with an average of 1 in 10 patients still meeting the criteria for malnutrition at 10‐years post‐Fontan surgery 10 …”
Section: Discussionsupporting
confidence: 88%
“…Most patients received an extracardiac Fontan conduit (62%) with 38% being fenestrated (Table 1). The median length of hospital stay was 12 days (IQR, [8][9][10][11][12][13][14][15][16][17][18]. Following surgery, 38% of patients had persistent pleural drainage lasting for >2 weeks.…”
Section: Perioperative and Postoperative Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Horsley et al found that after VAD implementation, the percentage of energy intake increased from 77% to 90% at 2 months, and the proportion of patients with malnutrition decreased significantly with improvement in BMI z scores. 119 Hollander et al found that in patients awaiting heart transplantation, those with VADs had a decrease in the presence of moderate to severe malnutrition compared with those treated with medical therapy alone. 120 Thus, in the heart failure population, implementing a VAD may improve nutrition provision both while awaiting and after transplantation.…”
Section: Heart Failure and Heart Transplantmentioning
confidence: 99%
“…Malnutrition is common in pediatric patients with heart failure who are listed for heart transplant (HT). It may persist for years after HT and is associated with increased morbidity and mortality 1–10 . Malnutrition is commonly treated with tube feeds with or without calorically dense feeds during the HT listing (HTL) period.…”
Section: Introductionmentioning
confidence: 99%